2020
DOI: 10.21203/rs.3.rs-115363/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postoperative Outcomes in Surgical COVID-19 Patients: A Multicenter Cohort Study

Abstract: BackgroundData on postoperative outcomes of the COVID-19 patient population is limited. We described COVID-19 patients who undergone a surgery and the pandemic impact on surgical activities.MethodsWe conducted a multicenter cohort study between March 13 and June 19 2020. We included COVID-19 patients who underwent surgery in nine centres of the Province of Québec, the Canadian province most afflicted by the pandemic. We also included suspected COVID-19 (subsequently confirmed not to have COVID-19) patients and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…9,10 Additionally, 30-day mortality has been shown to be lower in asymptomatic COVID-19 patients undergoing surgery (5.6%, compared to 23.1% in symptomatic patients; P = .118). 10 These data support the assumptions upon which our protocol was based.…”
supporting
confidence: 67%
“…9,10 Additionally, 30-day mortality has been shown to be lower in asymptomatic COVID-19 patients undergoing surgery (5.6%, compared to 23.1% in symptomatic patients; P = .118). 10 These data support the assumptions upon which our protocol was based.…”
supporting
confidence: 67%
“…Outside of microsurgery, SARS‐CoV‐2‐postive surgical patients have been found to be at increased risk for morbidity and mortality in the post‐operative period relative to SARS‐CoV‐2‐negative patients (Carrier et al, 2021; Collaborative CO, 2020b; Covidsurg Collaborative GC, 2021; Doglietto et al, 2020; El‐Boghdadly et al, 2021; Haffner et al, 2021; Katsiampoura et al, 2020; Phelps et al, 2020; Prasad et al, 2021). Specifically, the international COVIDSurg Collaborative demonstrated that pre‐operative SARS‐CoV‐2‐vaccination led to reduced risk of both post‐operative morbidity and mortality in SARS‐CoV‐2‐positive surgical patients (Collaborative CO, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its impact on pre‐operative management and procedure selection, SARS‐CoV‐2 may also negatively impact surgical outcomes (Katsiampoura et al, 2020; Phelps et al, 2020). Previous studies have shown that 30‐day mortality and complications, including thrombosis, are significantly increased in patients who have undergone surgery while infected with COVID‐19 (Carrier et al, 2021; Doglietto et al, 2020). More specifically, prior studies have shown that SARS‐CoV‐2 may increase risk for thrombotic events via induction of a pro‐coagulable state which, when combined with the pro‐inflammatory environment induced by surgery, can contribute to formation of deep vein thrombi, pulmonary emboli, and large vessel strokes (Abou‐Ismail et al, 2020; Janardhan et al, 2020; Mucha et al, 2020; Zapata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We found the postoperative 30-day mortality rate to be 4.01%, which was lower than the previous studies reporting mortality rates ranging from 14.7% to 27.3%. [4][5][6][7][8][9][10][11][12] We believe that this difference can be explained by the differences in the study periods, as well as better understanding of the care of patients with COVID-19 and development of perioperative management protocols over time. As our study included patients who had interventions in the height of the pandemic (January 2020 to March 2021), we were able to include a possibly larger proportion of patients who were vaccinated and as a result had asymptomatic/milder disease.…”
Section: Discussionmentioning
confidence: 99%